Crystal growth and magnetic characterization of HoIr2Si2 (I4/mmm). (28th August 2018) - Kliemt, K; Bolte, M; Krellner, C
Abstract: Single crystals of HoIr2 Si2 with the body-centered ThCr2 Si2 -type structure ( I 4/ mmm ) were grown by Bridgman method from indium flux. Single crystal structure determination yielded a Si-z position of 0.378(1) in the structure. We excluded the presence of the high temperature phase with the primitive CaBe2 Ge2 -type structure ( P 4/ nmm ) by powder x-ray diffraction. Magnetic measurements on the single crystals yield a Néel temperature of K. In the inverse magnetic susceptibility a strong anisotropy with Weiss temperatures K and K occurs above T N . The effective magnetic moment and is close to the expected value for a free Ho 3+ ion, . The field dependent magnetization shows a step-like behaviour due to crystalline electric field effects. The temperature and field dependence of the magnetization hint to the ordering of the magnetic moments along the c direction below T N .